Hubungan Pengetahuan Dengan Keikutsertaan Ibu Dalam Kegiatan Kelas Ibu Balita Di Desa Karangwedoro Wilayah Kerja Puskesmas Turi Kabupaten Lamongan - Kustini; Siti Sholikah; Marsheila Indriyana (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: Toddler mother class is a group learning activity in a class with several mothers who have children under five (aged 0-5 years) under the guidance of one or several facilitators (teachers) using the MCH handbook as a learning tool. The purpose of this research is to find out the relationship between knowledge and mother's participation in toddler mother class activities in Karangwedoro village, the working area of ​​the Turi Health Center in 2023   Methods : This study aims to determine the relationship between variables using a cross sectional approach. The variables to be studied are knowledge, attitudes and work (Independent Variables) with the participation of mothers under five classes (Dependent Variable) carried out at the same time   Results: , Based on the results of research that has been conducted in Karangwedoro Village, Turi Health Center Work Area, it can be concluded that there is a relationship between mother's knowledge and mother's participation in toddler mother class activities in Karangwedoro village, Turi Health Center Work Area in 2022 Conclusion: It is hoped that later the results of this research can be used as a source and input for program holders to further improve class activities for mothers of toddlers and improve routine and scheduled activities for mothers of toddlers classes and increase skills in delivering material in the mother of toddlers class module by attending trainings on mother class toddlers as well